Muscle Strength, Power, and Torque Deficits in Children With Type SS Sickle Cell Disease. Issue 5 (July 2018) - Dougherty, Kelly A.; Bertolaso, Chiara; Schall, Joan I.; Smith-Whitley, Kim; Stallings, Virginia A.
Abstract : In African-American children aged 5 to 17 years with and without type SS sickle cell disease (SCD-SS), dominant hand maximal handgrip strength, peak power, and plantar flexion isometric maximal voluntary contraction (MVC) torque were compared with adjustments for body size and composition. Children with SCD-SS (n=21; age, 11±1 y) compared with healthy control children (n=23; 10±1 y) did not differ by age, sex, or maturation stage, but had significantly lower Z scores for height, weight, body mass index, arm circumference, upper arm muscle area, and lean mass-for-height. Children with SCD-SS had significantly lower unadjusted handgrip strength (16±2 vs. 23±2 kg, P <0.01), peak power (1054±107 vs. 1488±169 W, P <0.04) and MVC torques at 2 angles (10 degrees: 27±3 vs. 42±5 Nm; 20 degrees: 21±3 vs. 34±4 Nm; all P <0.05). Performance decrements persisted when handgrip strength was adjusted for lean body mass and fat mass explaining 66% of the variance; peak power adjusted for age, lean body mass, fat mass, and height explaining 91% of the variance; and the highest MVC torque (10-degree angle) adjusted for left leg length, lean mass-for-height, and fat mass-for-height Z scores explaining 65% of the variance. This suggests additional factors contribute to the attenuated anaerobic performance.